THE USE OF BIOLOGICAL INDICATORS IN GEOGRAPHICAL RESEARCH - Abrantes, Angelica Scheffer da Motta [UNESP]; Piroli, Edson Luis [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
The increasing socio-environmental problems related to soil degradation, water quality and human health emphasize the need for studies with multidisciplinary characteristics capable of clarifying the effects of land use and management dynamics and their impacts on natural resources. Urban and agricultural growth, with the disorderly occupation of river basins, generates one of the greatest environmental and, consequently, socioeconomic impacts: erosion and consequent sediment production. The information about sediment quality is important for understanding environmental degradation processes. Thus, the objective of this work is to analyze the potential of the use of biological indicators in geographic research, through the microbiological quality of sand used in construction. In order to understand the socio-spatial aspects that contributed to the different transformations occurring in space, the aforementioned biological indicators were used in conjunction with the production of space as a possibility for such understandings, as well as the mapping of land cover and use of the municipality of Ribeirao Clear / PR. The results show that the hydrographic basins where the studied ports of sand are located are very altered, fact that results in the compromise of the microbiological quality of the sand used in the civil construction.
Keywords: Microbiological quality of sand; Production of space; Sediments